2006
DOI: 10.1038/sj.onc.1210114
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine-mediated migration of melanoma cells towards lymphatics – a mechanism contributing to metastasis

Abstract: The mechanisms that cause tumors such as melanomas to metastasize into peripheral lymphatic capillaries are poorly defined. Non-mutually-exclusive mechanisms are lymphatic endothelial cell (LEC) chemotaxis and proliferation in response to tumor cells (chemotaxis-lymphangiogenesis hypothesis) or LECs may secrete chemotactic agents that attract cancer cells (chemotactic metastasis hypothesis). Using migration assays, we found evidence supporting both hypotheses. Conditioned medium (CM) from metastatic malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
140
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 28 publications
7
140
0
1
Order By: Relevance
“…Recent studies have identified lymphatic density of the primary tumour upon excision as a potential predictor of metastasis (Dadras et al, 2003;Shields et al, 2004). This increased lymphatic density may be brought about by growth of new lymphatics towards tumours expressing VEGF-C or VEGF-D (Skobe et al, 2001), by stochastic variation of melanomas or metastatic chemotaxis towards lymphatic endothelial cells (Shields et al, 2007). The identification of increased lymphatic density has been combined with thickness and lymphatic invasion to generate a prognostic index (Shields' index) that predicts the likelihood of metastasis, at least in a relatively small number of patients .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified lymphatic density of the primary tumour upon excision as a potential predictor of metastasis (Dadras et al, 2003;Shields et al, 2004). This increased lymphatic density may be brought about by growth of new lymphatics towards tumours expressing VEGF-C or VEGF-D (Skobe et al, 2001), by stochastic variation of melanomas or metastatic chemotaxis towards lymphatic endothelial cells (Shields et al, 2007). The identification of increased lymphatic density has been combined with thickness and lymphatic invasion to generate a prognostic index (Shields' index) that predicts the likelihood of metastasis, at least in a relatively small number of patients .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the increase in lymphatic surface area increases the chances of intravasation and subsequent dissemination of neoplastic cells [19]. A recent study by Shields et al described both lymphatic endothelial cell (LEC) chemotaxis and proliferation in response to metasatic melanoma cells and secretion by endothelial cells of chemotactic agents that attract melanoma cells, suggesting that bidirectional interactions between these partners may promote lymphatic invasion [20]. Consistent with this hypothesis, the present study unequivocally showed that lymphatic invasion is common in primary VGP melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…43 LEC chemotaxis and proliferation in response to tumor cells (chemotaxis-lymphangiogenesis hypothesis) may occur or LECs may secrete chemotactic agents that attract cancer cells (chemotactic metastasis hypothesis). 44 Melanoma cells seem to grow more toward regions of high LEC density owing to chemotactic LEC secretions, including the chemokine CCL21. 44 We propose that increased iNOS and the possible consequent increased NO levels being associated to an augmented number of lymphatic vessels, might contribute to lymphangiogenesis in melanoma.…”
Section: Discussionmentioning
confidence: 99%